Sikap Petani Anggota Subak terhadap Program Asuransi Usahatani Padi di Subak Yeh Embang, Desa Yeh Embang Kangin, Kecamatan Mendoyo, Kabupaten Jembrana - KADEK AGUS NOPTANDIKA KUSUMA; I GEDE SETIAWAN ADI PUTRA; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Subak Farmers' Attitudes toward Rice Farming Insurance Program in Subak YehEmbang, Yeh Embang Kangin Village, Mendoyo Sub-district, Jembrana Regency Food security becomes one of the main goals of national development. One of theefforts undertaken by the Jembrana Regency Government is to implement a specialeffort (UPSUS) which is the insurance program of paddy farming (AUTP) since 2015.Farmers of Subak Yeh Embang who have not followed the insurance program of ricefarming is high (41.46%). The purpose of this research is to investigate the attitude ofthe farmers of Subak Yeh Embang on paddy farming insurance program. The researchwas conducted in Subak Yeh Embang, Yeh Embang Kangin Village, Mendoyo Subdistrict,of Jembrana Regency. The respondents were 35 people from the population of233 farmers who have not followed the paddy farming insurance program determinedby using the Proportional Random Sampling method.The findings showed that the attitude of farmers of Subak Yeh Embang can becategorized as agreed with the rice farming insurance by the score of 4.06. The farmers'attitude toward the objectives, targets, benefits, risks, and success of paddy farminginsurance program included in the category of strongly agree, while farmers' attitude tocompensation, compensation payment, coverage period, amount of claim, and theapproval of the insurance claim are included in the category agreed, and the attitude offarmers to the organization of the implementation of rice farming insurance programwas the category of doubtful.Based on the result of the research, it is expected that the extension agents and relatedinstitutions should be more active in conducting counseling and dissemination ofinformation about rice insurance program (AUTP).